Composición química, degradabilidad y cinética ruminal in situ de la caraca (Erythrina poeppigiana) en diferentes periodos de corte. - Díaz Romero, Vanessa Estefanía (2019)
The research was carried out in the experimental farm "La María" Rumiology and Nutritional Metabolism Laboratory (RUMEN) of the State Technical University of Quevedo (UTEQ), Faculty of Animal Sciences (FCP), located at km 71/2 via Quevedo - El Empalme, Province of Los Ríos, at 01º 06` 30 "south latitude and 79º 29` 30" west latitude and at an altitude of 73 masl. The chemical composition, degradability and ruminal kinetics in situ (MS, PC, MO, NDF and FDA) of the caracara (Erythrina poeppigiana) were evaluated in different cutting periods (30, 45, 60, 75, 90 and 105 days). A completely randomized design (DCA) was applied with four repetitions and for the differences between Tukey means (P≤0.05). The MS; MO e MI were not affected (P˃0,05) by the cut-off periods evaluated. Likewise, the in situ degradability of the MS was not affected by the cutting periods. The highest degradability (P <0.05) of OM was recorded at 45 days of regrowth age and at 6 hours of incubation (97.20%). However, the highest values for in situ degradability of the NDF are recorded at 30 days of age of the regrowth at 48 hours of incubation (88.18%). the highest values for the in situ degradability of the FDA are registered at 30 days of regrowth at 48 hours, (67.46%). The highest (P <0.05) Effective Degradability (SD: 2, 5 and 8% / hour) of the MS and MO was recorded at 30 and 45 days of regrowth age (93.70, 92.06, 90 , 49-91.37; 88.82; 86.41%, in order), but the highest values for NDF and ADF were recorded at 30 days of regrowth age (81.84, 77.30, 73 , 40-59.99, 57.47, 55.16%, in order). Key words: Caraca, ruminants, nutrition, feeding, degradability, kinetics